2004
DOI: 10.1021/om030619k
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Properties of a Superphane with One Thiophene and One CpCo-Stabilized Cyclobutadiene Ring

Abstract: A superphane consisting of one thiophene ring and one CpCo-stabilized cyclobutadiene ring, 8, was prepared in an eight-step synthesis from 5-cyclodecynol protected with tertbutyldimethylsilyl, 13. The first key step in this sequence was the reaction of 13 with zirconocene and subsequently with S 2 Cl 2 to yield the tricyclic thiophene derivative 12. The second key step was the ring closure of 11 with CpCo(COD) to give 8. X-ray structural investigations of 11 and 8 confirmed the structural assignments. Evidence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…After protection of the acidic proton in 25 by a cyano group, the stage was set to reduce the lower part of 26 by a phenylcopper reagent. This reaction afforded 27, which was transferred to the [10]cyclophenacene 28.…”
mentioning
confidence: 99%
“…After protection of the acidic proton in 25 by a cyano group, the stage was set to reduce the lower part of 26 by a phenylcopper reagent. This reaction afforded 27, which was transferred to the [10]cyclophenacene 28.…”
mentioning
confidence: 99%
“…In Figures and we show as an example the molecular structures of 11 and 13 . The structure of 8 was previously reported . In the molecular structures of 8 − 12 the propandiyl bridges at the positions α to the sulfur atom adopt a conformation in which the central CH 2 groups of the chains point away from the heteroatom (see Figure ).…”
Section: Resultsmentioning
confidence: 91%
“…Syntheses. Our previous studies showed that the best way to synthesize 8 − 13 is by starting with the tricyclic diyne 19 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations